O ISS e os clubes de futebol - Yunes Junior, Faissal (2020)
The Federal Constitution of 1988 (CF/1988), in particular, the chapter entitled National Tax System, establishes principles based, fundamentally, on the preservation and maintenance of values essential to the functioning of the State through taxation, always taking into account the constitutional limitations of the power to tax, taxpayer guarantees. Likewise, it attributes tax competence to political persons, but on the other hand it limits the power to tax in expressly established cases, via constitutional immunity and principles. Among others, the Union, the States, the Federal District and the Municipalities are prohibited from instituting taxes on the patrimony, income or services of non-profit education and social assistance institutions, provided that the requirements of the complementary law are met. In Brazil, the vast majority of football clubs are constituted under the non-profit association regime, achieved, therefore, as a rule, by tax immunity, under the terms of the national tax code. In particular, the Tax on Services (ISS), had its competence attributed to the Municipalities and the Federal District, under the terms of article 156, III, of CF/1988, however, these political entities must faithfully obey the constitutional rules, whether for incidence, whether for non-incidence of tax, taking into account the parameters established in Complementary Law, in this case LC 116/2003, with changes introduced by LC 157/2016. In view of this, the present study is dedicated to the analysis of the incidence, or not, of the ISS on the activities and revenues earned by football clubs, considering the immunity rules and complementary legislation. To do so, initially, it deals with constitutional issues and main aspects of ISS. Continuous act, examines the compatibility between the tax immunity established in the CF for educational and assistance associations, and its eventual application to football clubs, considering their social function. Finally, based on specific cases, it identifies deadlocks that would prevent the application of this legislation, detailing the relevant discretions for the identification of a possible incidence, or not, of the ISS, for taxation on the various revenues earned by Football Clubs